Disaster preparedness in Zimbabwe: a case of Muzarabani dsitrict - Tawona, Tapiwa D. (Midlands Sate University, 2015)
Both natural and human induced or man made disasters have negative effects on people’s lives because they cause loss of life and livelihoods, loss and damage of property, infrastructure like roads. Given this one can note that there is need to put in place measures to reduce and prevent whenever possible these adverse impacts of disasters on communities. It is against this background that this research focuses on assessing the disaster preparedness level of the Muzarabani community in Mashonaland central province in Zimbabwe. The qualitative data and information that was used in this research was gathered using interviews, questionnaires and observations. The study was done with fifty (50) participants who were chosen using purposive sampling. The findings shows that the most common and recurrent disasters in the Muzarabani area are floods, droughts, epidemics like cholera and other biological disasters like foot and mouth, anthrax. Human animal conflicts are also common but not as disastrous as floods and droughts. The participants also revealed that there are various disaster preparedness measures and activities being undertaken in the district by government and other stake holders. The findings also shows that a national disaster risk management plan exist at the district administrator’s offices. The district also has a district disaster risk management plan. The findings showed that effective early warning systems and effective disaster preparedness activities are derailed by lack of adequate financial resources. The district is not fully prepared for other disasters though it is fully prepared for some of the disasters that affect the district.